2022
DOI: 10.1007/s00146-022-01469-0
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach to detecting fraudulent job types

Abstract: Job seekers find themselves increasingly duped and misled by fraudulent job advertisements, posing a threat to their privacy, security and well-being. There is a clear need for solutions that can protect innocent job seekers. Existing approaches to detecting fraudulent jobs do not scale well, function like a black-box, and lack interpretability, which is essential to guide applicants’ decision-making. Moreover, commonly used lexical features may be insufficient as the representation does not capture contextual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The F1 score includes the harmonic mean of precision and recall, and its value ranges from 0 to 1, with 1 being the best possible score (El-Hasnony et al, 2022). It balances the precision and recall value, providing a single value that considers both false positives and false negatives (Naudé et al, 2023). This is particularly important in scenarios like pothole detection for autonomous vehicles, where correctly identifying potholes is crucial for safety, and false negatives (missing actual potholes) can have significant consequences (Naudé et al, 2023).…”
Section: F1 Scorementioning
confidence: 99%
See 1 more Smart Citation
“…The F1 score includes the harmonic mean of precision and recall, and its value ranges from 0 to 1, with 1 being the best possible score (El-Hasnony et al, 2022). It balances the precision and recall value, providing a single value that considers both false positives and false negatives (Naudé et al, 2023). This is particularly important in scenarios like pothole detection for autonomous vehicles, where correctly identifying potholes is crucial for safety, and false negatives (missing actual potholes) can have significant consequences (Naudé et al, 2023).…”
Section: F1 Scorementioning
confidence: 99%
“…It balances the precision and recall value, providing a single value that considers both false positives and false negatives (Naudé et al, 2023). This is particularly important in scenarios like pothole detection for autonomous vehicles, where correctly identifying potholes is crucial for safety, and false negatives (missing actual potholes) can have significant consequences (Naudé et al, 2023). In pothole detection for autonomous vehicles using YOLOV8, the F1 score becomes a critical metric for model performance evaluation (Bosurgi et al, 2022).…”
Section: F1 Scorementioning
confidence: 99%
“…The research found that the organizational type of feature is the best feature in detecting recruitment fraud as an independent model. Research conducted by Naude et al also focuses on detecting fake job recruitment types using the Gradient Boosting algorithm and using the steamy empirical rule set feature part-of-speech tags and bag-of-words vectors [18]. The research succeeded in achieving an F1 score of 88%.…”
Section: Introductionmentioning
confidence: 99%